Childhood social environmental and behavioural predictors of early adolescent onset cannabis use. (5th May 2020) - Scholes‐Balog, Kirsty E.; Hemphill, Sheryl A.; Heerde, Jessica A.; Toumbourou, John W.; Patton, George C.
Abstract: Introduction and Aims: This study prospectively investigates behavioural and social antecedents of different patterns of adolescent cannabis use, specifically, early adolescent onset cannabis use and late onset occasional use. Design and Methods: The sample comprised 852 adolescents (53% female) drawn from the Australian arm of the International Youth Development Study. Data were collected via self‐report surveys. Risk and protective factors from a modified version of the Communities That Care youth survey were measured in fifth grade (mean [ M ] = 10.9 years, SD = 0.4). Frequency of cannabis use was measured at six time‐points throughout adolescence (ages 12–19 years). Results: Early adolescent onset cannabis use (10.7% of the sample [ n = 91]) was predicted by childhood family‐related factors including poor family management, family history of antisocial behaviour and attachment to parents. Cigarette use and drinking until drunk were the strongest predictors of early adolescent onset cannabis use. Cumulative risks associated with community, family, peer/individual environments and early substance use (cigarettes, alcohol) in childhood were predictive of early adolescent onset cannabis use (e.g. relative risk ratio = 2.64; 95% confidence interval 1.40–4.97 for early substance use). Family and early substance use‐related cumulative risks were predictive of late adolescent onset occasional cannabis use ( n = 231; 27%). Cumulative early substance use risk was the strongest independent predictor of both early adolescent onset and late adolescent onset occasional cannabis use. Discussion and Conclusions: Primary prevention efforts should focus on reducing exposure and access to licit substances during late childhood and delaying the onset of use. Prevention and intervention targeted toward the family environment also appears likely to be important in the prevention of early adolescent onset cannabis use.